Severe snakebite envenomation in French Guiana: When antivenom is not available. (May 2018) - Kallel, Hatem; Mayence, Claire; Houcke, Stéphanie; Mathien, Cyrille; Mehdaoui, Hossein; Gutiérrez, José María; Megarbane, Bruno; Hommel, Didier; Resiere, Dabor
Abstract: In French Guiana, Bothrops atrox, Bothrops brazili, Bothrops bilineatus, Lachesis muta and Micrurus sp are responsible for most cases of snakebite envenomation. The clinical features in patients suffering from envenomations by viperid snakes involve local tissue damage and systemic manifestations, such as hemorrhage, coagulopathies and hemodynamic instability. We report a severe case of envenomation in a patient bitten by a large unidentified pit viper in French Guiana. Due to lack of antivenom, the patient only received symptomatic management. Severe manifestations of local and systemic envenomation developed, and the patient needed multiple debridement procedures and ultimately required a transfemoral amputation. In addition, Aeromonas hydrophila was cultivated from the affected tissue, suggesting that infection contributed to necrotizing fasciitis. This case highlights the clinical features of a severe viperid snakebite envenomation, and illustrates the urgent need to ensure accessibility of effective and safe polyvalent viperid antivenom in French Guiana. Highlights: Snake envenomation is an underestimated public health issue in Central and South America, with estimated 70, 000 cases yearly. In French Guiana, snake bite is an understudied public health problem. In the Amazonian region, severe snakebites are caused by B.atrox, B.brasili, B.bilineatus, L.muta and Micrurus spp. Our patient presented extensive muscular and cutaneous necrosis with multiorgan failure. He did not received antivenom. According to our case and to a recent death from snakebite, antivenom therapy is currently used in French Guiana.